GLOBAL GOVERNANCE AND THE CHALLENGE OF MULTIPOLARITY - Chachane, Harsha (International Journal of Research -GRANTHAALAYAH, 2025)
The emergence of multipolarity in the 21st century has redefined the dynamics of global governance. With the decline of unipolar dominance and the rise of multiple centers of power—such as China, India, the European Union, and regional coalitions—global governance systems are undergoing structural transformation. This study examines how multipolarity influences institutional cooperation, decision-making legitimacy, and geopolitical stability. Using a mixed-method analytical model based on international institutional performance and hypothetical survey data from 12 countries, the findings indicate that while multipolarity enhances representational inclusivity, it simultaneously creates coordination dilemmas and power fragmentation. The paper concludes that successful global governance under multipolarity requires adaptive multilateralism, equitable institutional reform, and renewed normative consensus.